Similar anaerobic and aerobic adaptations after 2 high-intensity interval training configurations: 10:5 s vs. 20:10 s work-to-rest ratio - Moghaddam, M.; Estrada, C. A.; Muddle, T. W.; Magrini, M. A.; Jenkins, N. D.; Jacobson, B. H. (The Journal of Strength and Conditioning Research, 2021)
This study compares the effects of 2 high-intensity interval training (HIIT) configurations, a 10-5 vs. a 20-10 second work-to-rest ratio, on anaerobic and aerobic performance. Thirty-four individuals were randomly assigned to 10-5-HIIT (n = 17) and 20-10-HIIT (n = 17) groups to complete 6 cycles of 6 exercises, 3 days a week for 4 weeks. The 10-5-HIIT was performed with 10 s:5 s work-to-rest ratio with 1-minute recovery between cycles, while the 20-10-HIIT was performed with 20 s:10 s work-to-rest ratio followed by a 2-minute recovery. Anaerobic (i.e., peak power [PP], anaerobic capacity [AC], anaerobic power [AP], and total work [TW]) and aerobic fitness (i.e., time to exhaustion [TE], absolute Vo2max [A-Vo2max], relative Vo2max [R-Vo2max]) were measured with pre-training and post-training intervention. A significant main effect time was observed for both 10-5-HIIT and 20-10-HIIT (p < 0.05) in PP (9.2%, 5.7%); AC (14.9%, 8.6%); AP (9.0%, 6.2%); TW (15.1%, 8.5%); TE (4.3%, 5.5%); A-Vo2max (9.4%, 8.9%); R-Vo2max (8.5%, 8.2%), respectively. In conclusion, individuals may be able to achieve similar health benefits as 20-10-HIIT by performing 10-5-HIIT, despite exercising for 50% less total time. High-intensity interval training has been suggested as a "time-efficient" mode of exercise that can mitigate the most significant barrier to physical activity, "lack of time." Both 10-5-HIIT and 20-10-HIIT can induce performance adaptations to a similar extent. However, because of shorter time commitment, performing 10-5-HIIT at 10 s:5 s work-to-rest ratio may offer a shorter and equally efficient interval. Functional fitness training during HIIT protocols seems to be as beneficial as ergometer-based HIIT to improve anaerobic and aerobic performance.